2017
DOI: 10.1590/1517-869220172301157903
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Adjustments of the Radial Nerve Are Intensity-Dependent

Abstract: Introduction: Peripheral nerve adaptation is critical for strength gains. However, information about intensity effects on nerve morphology is scarce. Objective: To compare the effects of different intensities of resistance training on radial nerve structures. Methods: Rats were divided into three groups: control (GC), training with 50% (GF1) and training 75% (GF2) of the animal's body weight. The morphological analysis of the nerve was done by light and transmission electron microscopy. One-way ANOVA and the T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 28 publications
3
12
0
Order By: Relevance
“…Nineteen articles published data about the maximum load‐carrying tests protocol (Antonio‐Santos et al., 2016; Carbone et al., 2017; Chi et al., 2020; Deus et al., 2012; Domingos et al., 2012; Gil & Kim, 2015; Gomes, Borges, Rossi, Moura, & Medeiros, 2017; Grans et al., 2014; Hornberger & Farrar, 2004; Kwon et al, 2018; Lim et al, 2018; Mônico‐Neto et al, 2015; Neves et al, 2019; Padilha et al, 2017; Padilha et al., 2019; Perrilhão et al, 2019; Prestes et al, 2009; Souza et al., 2014; Souza et al, 2017). LRT presented a positive effect on the maximum load‐carrying capacity (16 studies, SMD 12.37, 95% CI [9.36, 15.37], p < .00001, I 2 = 90%, Figure 11).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nineteen articles published data about the maximum load‐carrying tests protocol (Antonio‐Santos et al., 2016; Carbone et al., 2017; Chi et al., 2020; Deus et al., 2012; Domingos et al., 2012; Gil & Kim, 2015; Gomes, Borges, Rossi, Moura, & Medeiros, 2017; Grans et al., 2014; Hornberger & Farrar, 2004; Kwon et al, 2018; Lim et al, 2018; Mônico‐Neto et al, 2015; Neves et al, 2019; Padilha et al, 2017; Padilha et al., 2019; Perrilhão et al, 2019; Prestes et al, 2009; Souza et al., 2014; Souza et al, 2017). LRT presented a positive effect on the maximum load‐carrying capacity (16 studies, SMD 12.37, 95% CI [9.36, 15.37], p < .00001, I 2 = 90%, Figure 11).…”
Section: Resultsmentioning
confidence: 99%
“…(2012) demonstrated that the LRT, without any additional load, is already sufficient to increase the load‐carrying capacity by the rodent, having its function enhanced by increasing the training load. In addition, morphological adjustments to peripheral nerves may explain, in part, the increase in muscle strength without necessarily increasing the size of the muscle or its fibers (Carbone et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…4 In addition to body pressure applied on hands, it's believed wrist position affects both ulnar and middle nerves. 12,13,14 An extended wrist posture may directly contribute to nervous tension. 12 Studies shown wrist greatest extension was verified when cyclist has lowest hand position, which could exacerbate potential for nerve damage.…”
Section: Methodsmentioning
confidence: 99%
“…12,13,14 An extended wrist posture may directly contribute to nervous tension. 12 Studies shown wrist greatest extension was verified when cyclist has lowest hand position, which could exacerbate potential for nerve damage. 4 Using a glove with upholstery can reduce the maximum pressure applied in hypothenar region by 10-20%.…”
Section: Methodsmentioning
confidence: 99%
“…After an incision, a fragment of ~0.5 cm in length from the tibial nerve was removed from the posterior portion of the right leg. Then, we fixed the nerve fragment in 2.5% glutaraldehyde solution in phosphate buffer (0.2 M, pH 7.3) for 3 h (Pianca et al, 2015 ; Carbone et al, 2017 ; Krause Neto et al, 2017b ). Subsequently, we washed the material three times with the same buffer solution for 5 min at a time.…”
Section: Methodsmentioning
confidence: 99%